ROUTLEDGE HANDBOOK OF SUSTAINABLE URBAN TRANSPORT (ROUTLEDGE, 2026)
The Routledge Handbook of Sustainable Urban Transport offers a stateoftheart, comprehensive overview of sustainable transportation modes, impacts, technologies and policy. Over time, the economic benefits of transport have been overshadowed by negative externalities on the environment, public health and communities. Today, transport is one of the major contributors to greenhouse gas emissions, and, with the growth in the number and size of cities, urban transport will be a critical infrastructure to develop sustainably.Sustainable urban transport poses a key topic of debate for politicians, the public and transport providers worldwide, as legacy vehicle technologies, power sources, infrastructure and habitual human travel behaviours render the decarbonisation of local and global transport systems inherently challenging. Featuring contributions from worldleading, international scholars, the chapters examine concepts, issues and ideas across three topic areas that reflect the increasingly diverse nature of current research and thinking in sustainable urban transport: urban transport sectors; challenges, issues and impacts; and technical, social and economic solutions. Each chapter provides an overview of current knowledge, identifies issues, discusses the relevant debates in sustainable urban transport and seeks to put forward a future research agenda in the field. This Handbook offers a single repository on the current state of knowledge, written from a practical perspective, utilising theory that is applied and developed using realworld examples.The Handbook is an essential reference for researchers, academics and students working in all areas of sustainable transportation, from policy and planning to technology, in addition to industry practitioners looking to develop their professional knowledge.
Keywords: Urban transportation -- Environmental aspects.; Urban transportation policy.; elektronické knihy; electronic books